The effect of small business leaders' organisational mindfulness and social learning on opportunistic behaviour to survive the COVID-19 pandemic - Lusiantoro, Luluk; Purwanto, Bernardinus Maria; Rostiani, Rokhima (Emerald Group Holdings Ltd., 2022)
Purpose: This research aims to test the relationships between organisational mindfulness, social learning and opportunistic behaviour of small business leaders during the COVID-19 pandemic. Design/methodology/approach: Semi-structured interviews were conducted with six small business leaders from various sectors to explore and better grasp the unprecedented phenomenon. An online survey on small business owners and managers in Indonesia was then employed as the main study, resulting in 291 valid responses for further analysis. The data were analysed using regression on SmartPLS 3.0 software. Findings: This research finds that organisational mindfulness and social learning have positive and significant associations with the ability of small business leaders to discover and exploit opportunities. The path analysis suggests that organisational mindfulness plays a pivotal role as it also partially mediates the relationship between social learning and opportunistic behaviour. Originality/value: This is the first paper to test the relationships between organisational mindfulness, social learning and opportunistic behaviour, particularly in the context of COVID-19 pandemic. This work also contributes by emphasising the critical linkages between internal and external capabilities triggered by small business leaders to survive the pandemic. © 2021, Emerald Publishing Limited.